The Effectiveness of Communication in University-Level Learning Activities - Faza Fitri Fadlia; Youwanda Hazari; Salsabila Lathifatunnisa; Himatul Jannah Aridho (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
The spread of the Covid-19 virus has resulted in changes to the education system in various educational settings, including universities. This phenomenon provides a change from face-to-face learning to online. To achieve success in online learning, various ways are needed to support this success, one of which is by maximizing communication between lecturers and students. In this regard, this study aims to find out more about the effectiveness of communication at the university level during online learning. The method of conducting this research uses a qualitative approach with literature study techniques. The research that has been done shows that the effectiveness of communication in learning activities at the university level is considered quite effective.